Моделювання процесів при екструзійній обробці рослинної сировини - Шевчук, Михайло Вікторович; Дашивець, Галина Іванівна; Shevchuk, Mykhailo; Dashyvets, Halyna (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто особливості моделювання процесів, що відбуваються під час екструзійної обробки рослинної сировини. Встановлено, що ефективність екструзійного процесу значною мірою залежить від фізико-механічних, теплофізичних і технологічних характеристик матеріалу, зокрема вологості, олійності, вмісту оболонки та структурної неоднорідності сировини. Узагальнено підходи до математичного опису фазових і тепломасообмінних перетворень у матеріалі під дією тиску, температури та механічного зсуву. Наведено аналітичні залежності, що дають змогу враховувати вплив технологічних характеристик сировини на перебіг процесу. /// EN: The article considers the theoretical foundations of process modeling during extrusion treatment of plant raw materials. It is shown that the efficiency of extrusion depends on the physical, mechanical, thermophysical, and technological characteristics of the material, in particular moisture content, oil content, husk content, and structural heterogeneity. Generalized analytical relationships are presented to describe phase transformations and heat-and-mass transfer processes occurring under the influence of pressure, temperature, and mechanical shear. It is substantiated that mathematical modeling makes it possible to predict processing duration, heating intensity, moisture change, and other parameters determining the quality of the final product. The study confirms that taking into account the structural features of raw materials is necessary for improving the accuracy of calculations and optimizing extrusion treatment modes. Modern technologies for processing plant raw materials are actively developing in the direction of energy-saving and intensive processes, among which extrusion processing occupies a special place. It allows simultaneously to carry out thermomechanical modification of raw materials, increase its digestibility, change structural and mechanical properties and form a final product with specified characteristics. However, the complexity of physicochemical transformations occurring during extrusion (changes in moisture, temperature, pressure, viscoplastic behavior of the material) complicates the analytical description and control of the process. Existing approaches to describing extrusion processes are often based on empirical dependencies or simplified models that do not fully take into account the multifactorial nature of the influences. This leads to limited accuracy in predicting process parameters and the complexity of optimizing extruder operating modes when processing different types of plant raw materials. In this regard, the scientific and applied task of developing and improving mathematical models that allow adequately describing extrusion processing processes taking into account the rheological properties of raw materials, heat and mass transfer and energy costs arises. The creation of universal approaches to modeling that ensure increased efficiency of the technological process, stable quality of the final product and reduced energy consumption is especially relevant. Thus, the problem lies in the insufficient accuracy of existing models of extrusion processing of plant raw materials and the need to develop more adequate mathematical descriptions for optimizing and controlling this complex technological process.
Modeling of processes in extrusion processing of vegetable raw materials
Keywords: екструзійна обробка; математичне моделювання; рослинна сировина; вологість; олійність; лушпинність; тепло- і масообмін; технологічні характеристики; екструдер; extrusion treatment; mathematical modeling; plant raw materials; moisture content; oil content; husk content; heat and mass transfer; technological characteristics; extruder